2015
DOI: 10.2298/gsgd140626002b
|View full text |Cite
|
Sign up to set email alerts
|

Recent extreme air temperature changes in Montenegro

Abstract: Changes in Europe's Temperature Extreme Values. In environmental researches several concerns on the evolution of temperatures. However, in the last decade we can observe intensification of extreme events, including that of temperatures. The present research investigates the evolution of extreme temperature values scaled at annual scale using frequency analysis on historical data. Three types of extreme temperatures were analyzed: annual minimum and maximum, and highest daily temperature fluctuation on annual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
2
13
0
2
Order By: Relevance
“…The increasing trends of the air temperature (T) are similar for Kaunas and Sarajevo WS, ranging from 0.052 0 C to 0.047 0 C. Increasing trends ware also detected for the annual amount of precipitation, ranging from 3.582 mm year -1 in Kaunas to 1.724 mm year -1 in Sarajevo, Annual sum of precipitation has increased by more than 100 mm in Kaunas for a period of 30 years . The observed air temperature and precipitation change patterns in Lithuania and B&H are consistent with the predominant trends in other areas of East Europe Bukantis ArūNas & Rimkus Egidijus, 2005;Jaagus et al, 2009;Branković et al, 2013;Burić et al, 2013;Tripolskaja & Pirogovskaja, 2013;Unkasevic & Tosic, 2013;Rutgersson et al, 2014) and with trends observed globally (Kharin et al, 2013;Trenberth et al, 2013;Jacob et al, 2018;Popov et al, 2018).…”
Section: Resultssupporting
confidence: 84%
“…The increasing trends of the air temperature (T) are similar for Kaunas and Sarajevo WS, ranging from 0.052 0 C to 0.047 0 C. Increasing trends ware also detected for the annual amount of precipitation, ranging from 3.582 mm year -1 in Kaunas to 1.724 mm year -1 in Sarajevo, Annual sum of precipitation has increased by more than 100 mm in Kaunas for a period of 30 years . The observed air temperature and precipitation change patterns in Lithuania and B&H are consistent with the predominant trends in other areas of East Europe Bukantis ArūNas & Rimkus Egidijus, 2005;Jaagus et al, 2009;Branković et al, 2013;Burić et al, 2013;Tripolskaja & Pirogovskaja, 2013;Unkasevic & Tosic, 2013;Rutgersson et al, 2014) and with trends observed globally (Kharin et al, 2013;Trenberth et al, 2013;Jacob et al, 2018;Popov et al, 2018).…”
Section: Resultssupporting
confidence: 84%
“…Индекси су израчунати употребом the second half of the 20th and at the beginning of the 21st century (Branković, Č. et al, 2013;Zaninovic, K. & Cindric, K., 2014;Burić, D. et al, 2014;Burić, D. et al, 2015 The indices were calculated using RClimDex (1.0) software package that had been developed at Climate Research Division Canada (Zhang, X. & Yang, F., 2004).…”
Section: подаци и методеmentioning
confidence: 99%
“…Studies in the Mediterranean and Submediterranean part of the Southeast Europe where Bosnia and Herzegovina is located have also reported an increase in warm temperature indices and a decrease in cold ones, thus indicating the warming of climate system during ТАТЈАНА ПОПОВ, СЛОБОДАН ГЊАТО И ГОРАН ТРБИЋ TATJANA POPOV, SLOBODAN GNJATO AND GORAN TRBIĆ вијека и на почетку 21. вијека (Branković, Č. et al, 2013;Zaninovic, K. & Cindric, K., 2014;Burić, D. et al, 2014;Burić, D. et al, 2015). Претходно наведено наметнуло је нужну потребу спровођења истраживање ове врсте у Босни и Херцеговини.…”
Section: Introductionunclassified
“…Studies showed that the warming of the climate system is present in the Southeast Europe region. The annual and seasonal air temperature analyses in Serbia, Croatia, Slovenia, Montenegro, and Greece showed pronounced and mostly significant positive trends in vast majority of areas in the second half of 20th and the beginning of 21st century (Ducić, et al, 2009;Ducić, et al, 2008;Bajat, et al, 2015;Branković, et al, 2013;Milošević, et al, 2013;Burić, et al, 2014;Mamara, et al, 2016). The overall positive trends in annual air temperatures are mainly caused by the high and statistically significant positive summer trends.…”
Section: Introductionmentioning
confidence: 99%